Trends in Survival of Patients With Uterine Serous Carcinoma From 1988 to 2011: A Population-Based Study. Issue 6 (1st July 2017) - Mahdi, Haider; Han, Xiaozhen; Moulton, Laura; Vargas, Roberto
Abstract : Objective: Our study used the Surveillance, Epidemiology, and End Result database to determine if the changes in treatment paradigm observed over the last 2 decades have improved outcomes in patients with uterine serous carcinoma (USC). Methods: Women with USC were identified using the Surveillance, Epidemiology, and End Result database from 1988 to 2011 (n = 8230) and grouped into 3 cohorts (1988–1997, 1998–2004, and 2005–2011). Disease-specific survival and overall survival were estimated. Kaplan-Meier survival curves and Cox regression models were used. Results: Disease-specific survival (59 vs 94 months vs not reached; P < 0.001) and overall survival (31 vs 37 vs 45 months; P < 0.001) improved over time. In univariable analyses, only those with stage I–III and those who reside in the Western or Central regions were noted to have improvement over time. In multivariable analyses when adjusting for age, race, marital status, stage, geographic location, cancer-related surgery, extent of lymphadenectomy, and adjuvant radiation, patients who received the diagnosis during 2005 to 2011 were 22% less likely to die of uterine cancer (hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.70–0.87; P < 0.001) and 17% less likely to die of any cause (HR, 0.83; 95% CI, 0.76–0.90; P < 0.0001) compared with patients who received a diagnosis during 1988–1997. Similarly, patients who received a diagnosis during 1998–2004 were 15% less likely to die of uterine cancer (HR, 0.85; 95% CI, 0.77–0.94; P = 0.0015) and 10% less likely to die of any cause (HR, 0.90; 95% CI, 0.83–0.97; P = 0.0048) compared with patients who received a diagnosis during 1988–1997. Conclusions: Changes in treatment trends for USC over the last 2 decades have resulted in an improvement in outcome especially those with stage I–III disease.